Effective Local Self-Governance Through Gram Panchayats: A Case Study from Rural India. Issue 2 (June 2019) - Kumar, Ajit
Abstract: This article explores the broad processes that facilitated the effectiveness of a Gram Panchayat (GP, institution of local self-governance), despite its location in a relatively underdeveloped region. By employing a qualitative case study method and drawing on interviews, observations and secondary data, the effective work of Ahana GP, notwithstanding political contradictions, is analysed. Three practice implications arising from this case study are: the significance of developing organic links between a community and its economy; building effective grassroots-level leadership; and addressing felt needs of a community within the complex development process. The findings may be useful for local level development practice in similar contexts, both in developed and developing countries.